Real estate - Jacobus, Charles J. (Thomson/South-Western, 2006)
This is a paperback and condensed version of Real Estate Principles. It prepares students to take the real estate licensing examination. This best-selling book introduces the fundamentals of real estate though a down to earth writing style with aundant examples throughout